Evaluation of The Implementation of Consulting Services as One of the Internal Audit Functions According To The 2024 Global Internal Audit Standards Domain V - Dwi Puspita Sari; Lufti Julian (Green Publisher Indonesia, 2026)
This research evaluates the implementation of consulting services as part of internal auditing functions in PT DYX (Persero) based on Domain V of the Global Internal Audit Standards (GIAS) 2024. Internal audit plays a crucial role in supporting organizational objectives through both assurance and advisory services. The consulting services provided by the internal audit function aim to improve governance, risk management, and operational efficiency. This study uses a qualitative case study approach, focusing on PT DYX’s internal audit services throughout 2024. The evaluation compares the current practices with the requirements outlined in GIAS 2024, specifically assessing how consulting services align with the standards set in Domain V. The findings highlight the effectiveness of internal audit consulting services in contributing to organizational value and improving internal controls, governance, and risk management. This research also provides recommendations for enhancing the implementation of these services to align with best practices and increase organizational maturity